An Investigation of the Development and Implementation of Teacher's Licensing in Saudi Arabia Based on Local Stakeholders’ Perceptions, Compared with International and Regional Practices - Hameedadin, Amal Abdullah (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)